IMPLEMENTATION OF A RAI-FRAILTY SCREENING ACROSS SURGICAL CLINICS: A QUALITY IMPROVEMENT INITIATIVE. Issue 12 (18th November 2016) - Tucker, Paula; Flink, Benjamin; Varley, Patrick; Hall, Daniel; Johanning, Jason; Clevenger, Carolyn; Tomolo, Anne; Arya, Shipra
Abstract : Background: The Risk Analysis Index (RAI) is a pre-operative screening tool to identify frail patients at risk for post-operative complications and mortality. Prior to this initiative, no frailty screening existed within the local setting. Objectives: The global aim is to standardize pre-operative screening for frailty across surgical clinics by utilizing the RAI. The specific aim is to attain 80% RAI-Frailty screenings by surgery providers within 12 weeks of implementation for patients scheduled for elective surgery. Methods: This initiative was piloted within a vascular surgery clinic at a southeastern medical center. Implementation strategies were developed, and the Model for Improvement with sequential Plan-Do-Study-Act (PDSA) cycles was utilized to achieve project aim. A cause-and-effect diagram was completed to understand the lack of RAI-Frailty screenings and identify areas for improvement among surgery providers. Interventions included: audit and feedback, RAI REDCap link integration within Electronic Health Record (EHR), and creation of a RAI-Frailty screening template. Results: PDSA Cycle 1 demonstrated a below target mean of 26.3%. During PDSA Cycle 2 and 3, a special cause variation was demonstrated by a shift of 15 points above the mean prompting the split of P-chart control limits. After splitting the control limits, a common cause variation revealed the change was sustained. Conclusions: RAI-Frailty screening was successfully implemented and sustained in the vascular surgery clinic utilizing audit and feedback and EHR modifications as strategies for change. Based on these findings, this screening initiative is being implemented across surgical clinics. Outcome measures are being evaluated to determine the clinical implications of this screening initiative.Figure 1 Figure 2